1962
DOI: 10.1139/z62-054
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Fauna of the Manitoulin Island Region: I. Arthropoda Parasitica

Abstract: The incidence of Anoplura, Diptera, Mallophaga, Siphonaptera, and Acarina infesting 947 hosts, captured between 1959 and 1961 on Manitoulin Island, Ontario, is recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In Minnesota, Green et al (1943) reported average infestations of more than 3000 ticks on snowshoe hare (Lepus americanus) in late summer, with as many as 16 000 ticks found on one animal. There are numerous published records for H. leporispalustris in Canada (Hewitt 1915;Hearle 1938;Bequaert 1945;Brown and Kohls 1950;Judd 1953;Scholten et al 1962;Wilson 1967;Martell et al 1969;Ko 1972a;Wright 1979;Jones and Thomas 1980;Gkoroba 1980) with few specifics on the life cycle and natural history. The most detailed studies on its natural history were carried out in Nova Scotia by Campbell and Glines (1979) in the laboratory and by Green et al (1943) and Campbell et al (1980) in the field in Minnesota and Nova Scotia, respectively.…”
Section: Haemaphysalis Leporispalustris (Packard)mentioning
confidence: 99%
“…In Minnesota, Green et al (1943) reported average infestations of more than 3000 ticks on snowshoe hare (Lepus americanus) in late summer, with as many as 16 000 ticks found on one animal. There are numerous published records for H. leporispalustris in Canada (Hewitt 1915;Hearle 1938;Bequaert 1945;Brown and Kohls 1950;Judd 1953;Scholten et al 1962;Wilson 1967;Martell et al 1969;Ko 1972a;Wright 1979;Jones and Thomas 1980;Gkoroba 1980) with few specifics on the life cycle and natural history. The most detailed studies on its natural history were carried out in Nova Scotia by Campbell and Glines (1979) in the laboratory and by Green et al (1943) and Campbell et al (1980) in the field in Minnesota and Nova Scotia, respectively.…”
Section: Haemaphysalis Leporispalustris (Packard)mentioning
confidence: 99%
“…Remarks. This species has also been recorded from Odocoileus virginianus (Scholten et al 1962), 0. v. borealis (Peters, 1933, and Cervus canadensis (Spencer, 1966).…”
Section: Ke Chung Kim and C F Weisseementioning
confidence: 75%
“…Megabothris acerbus Holland 1949a:159 (ONT), Jellison et al 1953:616 (none), Sturm 1953:140, Benton and Krug 1956:9, 22 (NY), Hubbard 1962c:109 (MA, MI, NY, ONT), Scholten et al 1962:606 (ONT), Benton 1963:10, Benton and Smiley 1963:4 (NY), Osgood 1964:31 (VT), Lawrence at al. 1965:4 (MI), Benton 1966:77 (NY), Holland and Benton 1968:257–258 (PA), Benton et al 1969:196 (NY), Main 1970:79 (MA, NH, VT), Benton et al 1971:92 (NY), Quackenbush 1971:16–17 (VT), Amin 1973:110, Haas and Wilson 1973:309 (WI), Benton and Kelly 1975:151 (NY), Amin and Sewell 1977:208–211 (none), Robert and Bergeron 1977:1575, 1578 (QUE), Benton 1980:101 (see Atlas), Payne and Jones 1982:218 (“New England”), Amin and Wagner 1983:232–233, Durden 1983:18 (none), Haddow et al 1983:109 (southeastern Canada, northeastern U.S.), Holland 1985:359–361 (MB, ON), Galloway and Christie 1990:456 (MB), Larson 1997:21 (ND), Scharf and Lederle 1998:196 (MI), Jameson 1999:227 (none), Eckerlin et al 2008:75 (PA), Lewis 2009:434–325 (southeastern Canada and northeastern U.S.).…”
Section: Results Systematic Entomologymentioning
confidence: 99%
“…Monopsyllus vison Wagner 1936a:199–200 (BC), 1936b:91 (none), Jellison and Kohls 1939:2022 (AK, YT), Hubbard 1940d:2 (OR), Fuller 1943:21 (MI), Jellison et al 1943:4 (MT), Stanford 1944:175 (UT), Hubbard 1947:234–236 (AK, BC, ID, MT, OR, UT), Holland 1949a:160–170 (AB, BC, NT, ONT, QUE, SK), 1949b:12, 1950a:2, 4 (BC), Bacon 1953:16 (none), Jellison et al 1953:616 (none), Benton 1955:365, Brown 1955:365 (none), Morlan 1955:110 (NM), Wiseman 1955:23 (WY), Benton and Krug 1956:9, Geary 1959:36–37 (NY), Stark 1959:191–192 (UT), Johnson 1961:11–12 (CO, ID, MN, OR, TN, and New York north to Maine), Scholten et al 1962:606 (ONT), Benton and Cerwonka 1963:11–12 (NY), Holland 1963:60 (AK, Canada), Buckner 1964:853 (MB), Osgood 1964:31–32 (VT), Lawrence et al 1965:5 (MI), Benton 1966:78 (NY), Karnes and Shoemaker 1966:39 (WV), Kinsella and Pattie 1967:234 (WY), Wilson 1967:351–352 (ONT), Brown 1968:495 (NB), Benton et al 1969:196 (NY), Woods and Larson 1969:33–34 (ND), Benton et al 1971:92 (NY), Quackenbush 1971:17 (VT), Tipton and Saunders 1971:18 (UT), Wilson and Johnson 1971:111 (MI), Haas 1972:275–278 (none), Haas and Wilson 1973:310 (WI), Haas et al 1973:282 (NM), Jellison and Senger 1973:50 (MT), Benton and Kelly 1975:152 (NY), Jellison and Senger 1976:90 (AK, AB), Robert and Bergeron 1977:1575, 1577 (QUE), Haas et al 1978:337, 1979:1824 (AK), Eads et al 1979:39 (CO), Benton 1980:109 (see Atlas), Haas and Wilson 1982:59–63, Haas et al 1982b:731 (AK), Holland 1985:335–341 (AK, AB, BC, LAB, MB, NT, QUE, SK), Haas and Wilson 1986:55 (AK), Ayala-Barajas et al 1988:76 (NM), Beaucournu et al 1988:67 (none), Lewis et al 1988:181 (OR, WA), Larsen 1992:421 (none), Larson 1997:27 (ND), Krasnov et al 2004a:234, 236 (none), Hastriter and Whiting 2005:419–430 (ID), Nelder et al 2005:472 (TN), Morrone and Acosta 2006:5 (none), Eckerlin 2016:300 (WV), Bergman et al 2019:18 (BC).…”
Section: Results Systematic Entomologymentioning
confidence: 99%
See 1 more Smart Citation